2004
DOI: 10.1523/jneurosci.4734-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in the Suicide Brain: mRNA Expression of Corticotropin-Releasing Hormone Receptors and GABAAReceptor Subunits in Frontal Cortical Brain Region

Abstract: Corticotropin-releasing hormone (CRH) and GABA have been implicated in depression, and there is reason to believe that GABA may influence CRH functioning. The levels of CRH, and mRNA for CRH-binding protein, CRH 1 , and CRH 2 receptors, as well as various GABA A receptor subunits (␣1, ␣2, ␣3, ␣4, ␣5, ␦, and ␥2), were determined in several frontal cortical brain regions of depressed suicide victims and nondepressed individuals who had not died by suicide. Relative to the comparison group, CRH levels were elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
236
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(262 citation statements)
references
References 64 publications
22
236
1
3
Order By: Relevance
“…Whether similar reductions in GAD or GAT-1 mRNA and protein are present in our cohort of depressed subjects is yet to be determined. Other recent reports suggest that alterations in GABA receptor subunits may be involved in the genetic pathophysiology of depression and suicide (Choudary et al, 2005;Henkel et al, 2004;Sen et al, 2004;Merali et al, 2004). Our preliminary observations of reduced mRNA for GABA receptor subunits in the dlPFC of the same subjects as studied here (Duman RS et al, unpublished observations) are in accord with our present findings on reduced density of GABA interneurons immunoreactive for CB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whether similar reductions in GAD or GAT-1 mRNA and protein are present in our cohort of depressed subjects is yet to be determined. Other recent reports suggest that alterations in GABA receptor subunits may be involved in the genetic pathophysiology of depression and suicide (Choudary et al, 2005;Henkel et al, 2004;Sen et al, 2004;Merali et al, 2004). Our preliminary observations of reduced mRNA for GABA receptor subunits in the dlPFC of the same subjects as studied here (Duman RS et al, unpublished observations) are in accord with our present findings on reduced density of GABA interneurons immunoreactive for CB.…”
Section: Discussionsupporting
confidence: 92%
“…It is also noteworthy that the majority (12 MDD and seven controls) of subjects investigated by Rajkowska et al (1999) were included in the present study. It is of further interest that our present observations on the deficit in GABA neurons found predominantly in the dlPFC and not in the ventrolateral ORB cortex are in agreement with the findings of Merali et al (2004) on region-specific reductions in the mRNA expression of GABA receptor subunits in depressed suicide victims. In this study, reductions in various subunits of GABAA receptors were found in the frontopolar cortex but not in the ventrolateral or dorsomedial prefrontal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…[43][44][45][46] The observation of a significant misexpression of molecules central to both GABAergic and glutamatergic neurotransmission in the cortical areas of individuals with major depression has been previously documented by several groups. 21,23,47 These studies follow on a body of clinical evidence showing that antidepressant medications may reduce glutamatergic activity while raising cortical GABA levels, which are seen to be reduced in major depression 48,49 and possibly also schizophrenia. 50,51 Since the two neurotransmitters are intimately connected by virtue of interconversion through glutamic acid decarboxylase in the synthesis of GABA from glutamate and the TCA cycle in the production of glutamate from GABA, it is difficult to disentangle the possible effects of these two molecules on the pathophysiology of depression and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes are of particular interest, GABA A receptor, a-1 (GABRA1) and GABA A receptor, b-1 (GABRB1) ( Table 3), as GABA receptors mRNA levels have been associated previously with depression and suicidality. 95 Inhibitory neurotransmission in the mammalian brain is mainly accomplished by gabaergic neurons, responsible for the release of GABA. 96 GABA neurotransmission modulates the activity of noradrenergic, dopaminergic and serotonergic systems.…”
Section: Discussionmentioning
confidence: 99%